Comparison of antioxidant, antibacterial and anti-proliferative activities and prebiotic effects of extracts from Red Pitaya (Hylocereous polyrhizus), White Pitaya (Hylocereus undatus) and Papaya (Carica papaya) - Mohd Adzim Khalili Rohin
Red pitaya fruit has generated a lot of interest as a source of functional food. This study was conducted to evaluate total phenolic content, antioxidant capacity and radical scavenging activity of the hexane, dimethyl sulfoxide (DMSO), ethyl acetate (EA) and methanol extracts of peel and flesh of red pitaya, white pitaya and papaya fruits. Their potential as antibacterial and antiproliferative agents inhibiting the growth of human promyelocytic leukaemia cells (HL-60), human colon adenocarcinoma cell line (HT-29), human breast adenocarcinoma cell line (MCF-7), human epithelial carcinoma cell line (HeLa) and maintaining the growth of 3T3 normal cell (mouse epithelial cell) were also studied. The composition of oligosaccharides in red pitaya and their effects in enhancing the growth, viability and activity of five strains of Bifidobacterium spp. in reconstituted skim milk and reinforced clostridial medium were evaluated. Antioxidant capacity study of the fruit extracts showed strong activity to inhibit lipid peroxidation as determined by ferric thiocyanate (FTC) and thiobarbituric asid (TBA) methods. At the given concentration, relatively higher activity was recorded in the extracts of the red pitaya fesh followed by red pitaya peel, white pitaya flesh; white pitaya peel, papaya flesh and papaya feel, surpassing the activity of common commercial antioxidant [?-tocopherol, butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT)]. Radical scavenging and reductive activities were higher in red pitaya flesh as compared to BHT and ?-tocopherol indicating that red pitaya flesh contained high amount of phenolic compounds. The reductive activity of extracts from the flesh were significantly (p<0.05) lower than ?-tocopherol, BHA and BHT. Antibacterial activity study showed that the methanolic extract of red pitaya flesh and peel had high inhibition against Staphylococcus epedermidis, Staphylococcus aureus, Pseudomonas aeruginosa and Salmonella typhimurium. Cytotoxic study indicated that crude extract from both flesh and peel of red pitaya, white pitaya and papaya have excellent potential as antiproliferative compounds against various cancer cell lines and can significantly inhibit the growth of HL-60, MCF-7, HT-29 and HeLa cancer cells. The methanol extract of red pitaya flesh has a broad spectrum of activity by inhibiting the growth of HL-60, MCF-7, HT-29 and HeLa cancer cells. The percentage of oligosaccharides in all fruit was higher in flesh as compared with the peel. The flesh of red pitaya was found to have highest concentration of oligosaccharides as compared with white pitaya and papaya but the numerical values ware not significantly different (p>0.05). This study indicated that obligosaccharides from red pitaya enhanced the growth activity of commercial strains of bifidobacteria typically used in manufacture of remented dairy products. The mean doubling time (Td) for Bifidobacterium longum, was lowest in the presence of red pitaya oligosaccharides compared with galactooligosaccharides (GOS), fructooligosaccharides (FOS) and inulin. Retention of viability of five bifidobacterium species was greatest in the presence of oligosaccharides from red pitaya followed by GOS, FOS and inulin. The highest percentages of acetic and lactic acids were produced by Bifidobacterium longum, Bifidobacterium infantis and Bifidobacterium adolescentis with red pitaya oligosaccharides. The pattern of results was similar to commercially available oligosaccharides (inulin, GOS, FOS). Therefore, this study provided promoting, and probiotic activity of natural oligosaccharides compound from red pitaya, white pitaya and papaya.